PostgreSQL 12 high availability cookbook : over 100 recipes to design a highly available server with the advanced features of PostgreSQL 12 - Thomas, Shaun (Packt Publishing, 2020)
Database outages are costly and largely avoidable. That's why it's important to apply time-tested high availability techniques. This book will help you design and build an indestructible PostgreSQL 12 cluster that can remain online even in the direst circumstances. You will learn to monitor and automate your way to reassuring high availability.